2018
DOI: 10.22159/ijpps.2018v10i3.22751
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic Fracture Risk in Rheumatoid Arthritis

Abstract: Objective: Osteoporosis is an extra-articular complication of rheumatoid arthritis (RA) with increased risk of fractures. FRAX is an online tool for assessing risk of osteoporotic fracture. However, the relationship between the FRAX score and disease specific risk factors has not yet been investigated in RA. Hence, we assessed 10-year fracture risk using FRAX and its relationship with disease activity score, inflammation and disease duration in RA.Methods: 50 RA patients enrolled and recruited consecutively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…The decrease in BMD causes increase in proximal femoral morphometry, and this may be due to cortical thinning, age-related bone loss, and dietary habit which increases the risk of hip fracture. The variations in FNAL may be related to the higher occurrence of hip fracture [18][19][20]. The present study found negative correlation between FN-BMD and FNAL.…”
Section: Discussionsupporting
confidence: 53%
“…The decrease in BMD causes increase in proximal femoral morphometry, and this may be due to cortical thinning, age-related bone loss, and dietary habit which increases the risk of hip fracture. The variations in FNAL may be related to the higher occurrence of hip fracture [18][19][20]. The present study found negative correlation between FN-BMD and FNAL.…”
Section: Discussionsupporting
confidence: 53%
“…Steroids were first used clinically to treat dermatological diseases due to their anti-inflammatory action. Corticosteroids are commonly indicated in treating various types of inflammatory and immune-mediated disorders such as adrenocortical insufficiency, rheumatic diseases [9], asthma, and skin diseases [10]. In dentistry, they are generally used to relieve pain, anxiety and for the management of oral lesions that are manifestations of systemic disorders [11].…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroids are commonly advised as replacement therapy in treating various types of inflammatory and immunosuppressive disorders. 4,5 Steroidal drugs are known to exert definite antiallergic, anti-inflammatory and immunosuppressive effects. 1 However, despite these beneficial actions, corticosteroids are also known to cause adverse reactions likerashes, clouding of the lens, weakness in the muscles, GIT disorders and candidiasis.…”
Section: Introductionmentioning
confidence: 99%